Heat Wave Adaptations: Unraveling the Competitive Dynamics Between Invasive Wedelia trilobata and Native Wedelia chinensis - Haochen Yu; Cheng Han; Guangqian Ren; Xuanwen Wu; Shanshan Qi; Bin Yang; Miaomiao Cui; Xue Fan; Zhaoqi Zhu; Zhicong Dai; Daolin Du (Plants)
Heat waves (HW) are projected to become more frequent and intense with climate change, potentially enhancing the invasiveness of certain plant species. This study aims to compare the physiological and photosynthetic responses of the invasive Wedelia trilobata and its native congener Wedelia chinensis under simulated heat wave conditions (40.1 °C, derived from local historical data). Results show that W. trilobata maintained higher photosynthetic efficiency, water-use efficiency (WUE), and total biomass under HW, suggesting that its ability to optimize above-ground growth contributes to its success in heat-prone environments. In contrast, W. chinensis focused more on root development and antioxidant protection, exhibiting a decrease in total biomass under heat wave conditions. These results indicate that W. trilobata employs a more effective strategy to cope with heat stress, likely enhancing its competitive advantage in regions affected by heat waves. This study highlights the importance of understanding species-specific responses to extreme climate events and underscores the potential for heat waves to drive ecological shifts, favoring invasive species with higher phenotypic plasticity.